Pension fund governance and the choice between defined benefit and defined contribution plans - Timothy Besley; Andrea Prat (Institute for Fiscal Studies (IFS), 2003)
Until recently, most policy debates on pensions — especially in Europe — focused on public responsibilities and the difficulties that many publicly funded schemes have in meeting their obligations. However, recent events, not least declines in stock markets, have increased the salience of such issues in privately funded pensions. This has major implications for countries, such as the U.S. and U.K. which have already gone heavily down the private funding route. However, it may also affect the attractiveness of this option as an alternative to public funding. The Pension Benefit Guaranty Corporation (PBGC) estimates that US companies have accumulated pension deficits of around 300 billion dollars. In the UK, Morgan Stanley estimates that the aggregate pension deficit of the FTSE 100 companies in the end of 2002 is 65 billion pounds. Serious deficits are also reported in private occupational plans in Germany and the Netherlands.
Keywords: 330; Rentenfinanzierung; Alterssicherung; Private Rentenversicherung; Theorie